The Effectiveness of Using Wayang Media in Increasing Elementary School Students' Knowledge About Dengue Fever Prevention - Bakti Wibowo; harisma Imami; Aisyah Nur Safitri; Rifqi Harimurti; Hanif Fikria Nabila; Alman Faluti Ashari; Farhan Fata Hillah; Amelia Saputri; Nabila Aurelia Nuraini (Journal of Health Community Service, 2023)
Dengue fever is caused by the dengue virus in the flavirus genus and family flaviviridae. Transmission of this disease through mosquito bites from the Genus aedes. Cases of dengue fever in Gresik increased by 30 people from 1 to 27 January 2022. The trigger for this disease is caused by poor environmental conditions such as lack of sunlight, humidity, and being close to rivers with slow flow. This research is aimed at elementary school students by conducting education using the fairy tale method which is packaged using the form of a puppet story. This research uses the Story telling method and Wayang.The design in this article is a Descriptive design which is a design that describes the object or subject being studied. The population of this study was elementary school students in grades IV and V totaling 61 people. The data analysis technique used is descriptive analysis. The results of the study showed that respondents were in the age group of ±10 years and 11 years. The largest number of respondents were in grade V of elementary school. Most respondents had a level of knowledge about Dengue Fever of 24% and increased to 30% after the delivery of the material. The conclusion of this study is that there is a significant increase in students' knowledge about Dengue Fever and it is hoped that with this counseling, students and residents of Banyuurip village can better maintain and pay more attention to their environment so that it remains clean.